Uterine necrosis during pregnancy following exploratory laparotomy. Issue 11 (1st November 2022) - Hirsch, Anna; Newman, Rachel; Naqvi, Mariam
Abstract : Uterine necrosis is an infrequent event and is most commonly reported as a complication of interventions for postpartum haemorrhage management. Cases of uterine necrosis in pregnancy are rare. The mainstay of treatment for uterine necrosis is hysterectomy, and the data regarding conservative management are limited. A gravida 3, para 2 presented at 33 weeks gestation with ovarian torsion and underwent an exploratory laparotomy with ovarian cystectomy. The surgery was complicated by excess bleeding, which was controlled with the placement of sutures along the uterine body. She had multiple subsequent presentations for severe abdominal pain without clear aetiology. Four weeks after the initial surgery, she underwent caesarean delivery, at which time uterine necrosis was diagnosed. Her uterus was preserved. She received postoperative intravenous antibiotics and was closely observed. She continued to do well 10 months postpartum. In patients with uterine necrosis during pregnancy who are haemodynamically stable, conservative management may be an option.